FTTH Network Expansion Modeling and Link Budget for Housing Locations - Safrianti, Ery; Mukti, Widyantoro Tejo (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
The location of the research was carried out at Villa Melati Permai II Housing which is on the Melati Indah Street, Tampan District, Pekanbaru City. Villa Melati Permai II is categorized as middle to upper-class housing but does not have its access network. This research will make the modeling of FTTH (Fiber To The Home) networks with network feasibility parameters to produce quality and appropriate FTTH networks. Manual calculation on the feasibility of FTTH networks using the power link budget and rise time budget shows results within the feasibility limit, which does not exceed the maximum limit for the power link budget of -27 dBm and rise time budget below the total time of bit rates. Calculation with NRZ (Non-Return to Zero) coding produces a downstream value of 0.2813 ns and upstream 0.562 ns. System performance parameters that show signal to noise ratio and bit error rate deliver good quality. Signal to noise ratio exceeds the minimum limit of PT. Telkom standard that is 21.5 dB and the bit error rate does not exceed the optical link standard which is 10-9. Good performance is also shown by eye pattern in optical simulation that displays amplitude signals with the same time and shows clear differences between bits 1 and bits 0.